Children's Motives for Admitting to Prosocial Behavior - Watanabe, Yayoi; Lee, Kayo (Frontiers in Psychology, 2016)
There has been extensive research on children’s moral evaluation of lying in prosocial situations. Current knowledge regarding the concept of lying has been derived from studies showing that cultural differences exist, whereby non-Western children tend to rate lie-telling more positively than Western children do. These findings suggest that there are different views about whether children should publicize their prosocial behaviors and that children have universal motivations when they admit to engaging in prosocial behavior. A gender difference has also been found in relation to prosocial behavior. However, previous studies did not investigate in detail children’s motivation for admission or non-admission to prosocial behavior, and if there is a gender difference. Therefore, this study examined the diversity in and development of motivations for admitting to engaging in prosocial behavior, with the aim of clarifying whether disclosing good deeds to teachers varies as function of children’s grade level in school, and how such motivations differ with age and gender. Questionnaires from 1,345 elementary and junior high school students in Japan were analyzed. Results showed that children’s communication tendency with regard to prosocial behavior reports peaked in the fourth grade of elementary school and gradually decreased thereafter. From the third grade of elementary school onwards, children reported that they refrained from this type of communication because they feared others’ negative evaluation and wanted to comply with modesty norms. Girls were more likely than boys were to believe that it is better to tell the truth about engaging in prosocial behavior, but boys and girls had largely the same motives for not owning up to performing a desirable deed.